Oxidative stress is the active pathway in canola seed aging, the role of oxidative stress in the development of seedlings grown from aged canola seed - Hora Naghisharifi; Maryam Kolahi; Mohamad Javaheriyan; Behrooz Zargar (Plant Stress, 2024)
The widespread use of canola in the food sector has led to accelerated product growth, making it the second largest crop in the world. The analysis showed an increase in the content of proline (13.6%), H2O2 (12.7%), the levels of lipid peroxidation (30.7%), and antioxidant capacity (25.7%) in aged canola seed. The activity of CAT, SOD, and GPX enzymes increased by 1.40, 2.51, and 5.93 times respectively, while GR activity decreased by 8.8% in aged canola seed as compared to the control. An increase in GSSG content to 2.57 times and a decrease in GSH content of 0.76 times were observed in aged canola seeds. The increase in oxidative stress indices and the activity of antioxidant enzymes in canola seeds under accelerated aging indicate the role of free radicals in aging. Amylase enzyme activity increased 2.57 times in aged canola seed. Oxidative stress causes changes in the biological structures of seeds including cell membranes, lipids, pfroteins, and even in different tissue layers of seeds, which form different dimensions of the aging process. The analysis of canola seeds under accelerated aging showed that although aging reduced seed germination by 70%, the seedlings obtained from the seeds with the ability to germinate showed changes in the metabolic pathways of carbohydrates (0.26 times reduction) and proteins (1.36 times increase) of the seedlings. The phenolic compounds, flavonoid, and flavonol content of seedlings from aged seeds increased by 12.7%, 12.4%, and 12.1%, respectively. These seedlings showed significant changes in oxidative stress indexes compared to the control seedling.